Glass, wax and metal : lighting technologies in Late Antique, Byzantine and medieval times - Motsianos, Iōannēs,; Garnett, Karen S., (Archaeopress archaeology., 2019)
This volume provides an extensive look at the technological development of lighting and lighting devices during Late Antiquity and the Middle Ages in Western Europe and Byzantium. 29 papers are gathered from two International Lychnological Association (ILA) Round Tables held in Olten, Switzerland (2007) and Thessaloniki, Greece (2011).